A maternal Western diet during gestation and lactation modifies offspring's microbiota activity, blood lipid levels, cognitive responses, and hippocampal neurogenesis in Yucatan pigs. Issue 5 (6th February 2017) - Val-Laillet, David; Besson, Marie; Guérin, Sylvie; Coquery, Nicolas; Randuineau, Gwénaëlle; Kanzari, Ameni; Quesnel, Hélène; Bonhomme, Nathalie; Bolhuis, J. Elizabeth; Kemp, Bas; Blat, Sophie; Le Huërou-Luron, Isabelle; et al.
ABSTRACT: A suboptimal early nutritional environment ( i.e., excess of energy, sugar, and fat intake) can increase susceptibility to diseases and neurocognitive disorders. The purpose of this study was to investigate in nonobese Yucatan minipigs ( Sus scrofa ) the impact of maternal diet [standard diet (SD) vs. Western diet (WD)] during gestation and 25 d of lactation on milk composition, blood metabolism, and microbiota activity of sows (n = 17) and their piglets (n = 65), and on spatial cognition (n = 51), hippocampal plasticity (n = 17), and food preferences/motivation (n = 51) in the progeny. Milk dry matter and lipid content, as well as plasma total cholesterol and free fatty acid (FFA) concentrations (P < 0.05) were higher in WD than in SD sows. Microbiota activity decreased in both WD sows and 100‐d‐old piglets (P < 0.05 or P < 0.10, depending on short‐chain FAs [SCFAs]). At weaning [postnatal day (PND) 25], WD piglets had increased blood triglyceride and FFA levels (P < 0.01). Both SD and WD piglets consumed more of a known SD than an unknown high‐fat and ‐sucrose (HFS) diet (P < 0.0001), but were quicker to obtain HFS rewards compared with SD rewards (P < 0.01). WD piglets had higher working memory (P = 0.015) and reference memory (P < 0.001) scores, which may reflect better cognitive abilities in the task context and a higher motivation for the food rewards. WD piglets had a smaller hippocampal granular cell layer (P = 0.03) and decreased neurogenesis (P < 0.005), but increased cell proliferation (P < 0.001). A maternal WD during gestation and lactation, even in the absence of obesity, has significant consequences for piglets' blood lipid levels, microbiota activity, gut–brain axis, and neurocognitive abilities after weaning.—Val‐Laillet, D., Besson, M., Guérin, S., Coquery, N., Randuineau, G., Kanzari, A., Quesnel, H., Bonhomme, N., Bolhuis, J. E., Kemp, B., Blat, S., Le Huërou‐Luron, I., Clouard, C. A maternal Western diet during gestation and lactation modifies offspring's microbiota activity, blood lipid levels, cognitive responses, and hippocampal neurogenesis in Yucatan pigs. FASEB J. 31, 2037–2049 (2017). www.fasebj.org